THE ONEIRIC TOPOS “SATELLITES” IN A. ZHURAKIVSKII’S NOVEL “SATELITY” AS A LOCUS OF ALLUSIVE-POSTMODERN SIMULATION (ALLUSIONS, QUOTES AND REMINISCENCES IN AMERICAN POPULAR CULTURE) - Strilchyk, B. A. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
This article regards the work “The Satellites” by Andrii Zhurakivskii as an object for literary and psychoanalytical analysis. In the text of this work we have formed the oneiric structure (according to chronotopic division into dream levels and sub-levels, as proposed by plot collisions) and have explicated fragments of ideological and mass-cultural discourse (that episodes being the part of the early 90th popular culture matrix and the ideological scheme of the criticism of capitalism, the methodology offered by Slavoi Zizek have been used), and, furthermore, have been analyzed the parallel «Zhurakivskii-Carroll» as the basis for image and archetype exchange, as well as the basis for creation of the post-modern textual discourse due to parodying, intertextuality, etc. Oneiric space of “The Satellites” by Andrii Zhurakivskii is full of the post-modern artifacts: calques of plot twists here correlates not only with Carroll, but with Tolkien, “The Matrix” by Wachowski brothers and lots of others popular culture phenomena from the late 90th and early 2000th. Thus, textual dream-picture as well is a field, where the post-modern play is held, and oneiric criticism is applicable to this play, as well as ideological, semiotic and psychoanalytic interpretation. Especially important are diffusional elements on the brink of hallucinations and dreams which play initial plot-building role and to some degree indicate the correlation between real and irreal chronotopes (within nonsonscious textual dimensions as well).